Penerapan Strategi Practice Rehearsal Pairs pada Pembelajaran IPS Siswa - Sari, Reni; Rosalina, Elya; Sofiarini, Andriana (JOEAI (Journal of Education and Instruction), 2021)
This study aims to determine the significant completeness of social studies learning outcomes for fifth grade students of SD Negeri 1 Air Satan after the Practice Rehearsal Pairs strategy was applied. The research method used is a quasi-experimental. The population in this study were all fifth grade students of SD Negeri 1 Air Satan totaling 51 students and the research sample was 25 students in grade IV, consisting of 10 male students and 15 female students taken by simple random sampling. Data collection techniques using multiple choice test techniques. Data analysis technique using t test. Based on data analysis, it was obtained that the average value of the Pre-test was 57 and the average value of the Post-test was 78.76 with a confidence level of 5%, it was obtained tcount = 3.776 and ttable = 1.771 because tcount> ttable then, Ha was accepted and Ho was rejected. From the results of data analysis, it was concluded that the social studies learning outcomes of fifth grade students of SD Negeri 1 Air Satan after the Practice Rehearsal Pairs strategy was implemented were significantly completed. Keywords: Practice Rehearsal Pairs strategy, Social Studies Learning Outcomes, Elementary School